Por entre práticas em movimento : um estudo etnográfico com professores de inglês em formação continuada - Souza, Lediane Manfé de (2014)
This study investigates cultural practices of public school English teachers participating in the course “Continuing Education of English Teachers: Critical Teaching”. It was developed under an ethnographic perspective through participant observation, interviews (informal conversations) and analysis of documentation. The purpose of this interpretative qualitative study is to understand how teachers bring their local practices into the course and make sense of their experiences motivated by discussions related to questions of teaching-learning over which they had the opportunity to reflect and, after reflection, give new meanings back to their own practices. Situated in the area of Applied Linguistics, this research is founded in ethnography as theory that, according to Harry Wolcott, can be understood as an attitude, “a way of seeing”, orientated by cultural theories. Two questions directed this research: 1. In what events teachers are engaged? 2. What do the events mean for those involved? The analysis shows that the teachers initially justified their chosen methodologies based on restrictions encountered in their contexts that refer to the obligation to complete the material and to cover the content and how they reacted giving new meanings to their practices starting from reflections on the continuing education course. The results suggest a move towards a greater role of the teacher in the in-between space in which they can reflect and decide on which way to go, what to keep and what to change, what works and what can be improved, a process, a movement, a third space where these practices intersect, sit, change, consolidate or not as a cultural practice. The results of this work contribute with a reflection of English teachers and AL researchers interested in teaching and the continuing education of public school English teachers.